Strategi Produk Keripik Dangke Melona dalam Penguatan UMKM Lokal di Kecamatan Cendana, Kabupaten Enrekang - Potton, Zainal (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Dangke is a traditional food from Enrekang Regency, South Sulawesi, with a texture and appearance similar to soft tofu, though it is not cheese. Strategic management aims to achieve organizational success by integrating areas such as information systems, marketing, management, production, finance/accounting, and R&D. The Keripik Dangke business requires advanced processing technology to compete with other types of chips made from different raw materials. This study aims to analyze product, pricing, and promotional strategies used by the Keripik Dangke Melona business in Cendana District, Enrekang Regency. Using a descriptive qualitative method, the research was conducted in Baba Hamlet, Cendana Village. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing. The findings show that the business applies product positioning, product design, and new product development strategies. For pricing, it uses competitive pricing. In promotion, the business employs digital marketing, direct marketing, and endorsement strategies.